Neglected Contributions to the Study of Kingship in the Pentateuch and the Deuteronomistic History - Levinson, Bernard M. (The formation of Biblical texts, 2024)
In a memorial volume for Professor Gary N. Knoppers, this chapter examines his neglected contributions to the study of kingship in the Pentateuch and in the Deuteronomistic History. His article, “Dissonance and Disaster in the Legend of Kirta,” investigates kingship in Ugaritic epic and gets at the larger question of royal ideology in the ancient Near East. His article, “Rethinking the Relationship between Deuteronomy and the Deuteronomistic History,” challenges any notion of the Deuteronomistic History as a passive or slavish implementation of the legal corpus of Deuteronomy. Levinson draws attention to the methodological contributions of Knoppers.